2012
DOI: 10.1016/j.cemconres.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of self-sealing in high-strength and ultra-low-permeability concrete in water using micro-focus X-ray CT

Abstract: High-strength and ultra-low-permeability concrete (HSULPC) is thought to be useful as a radioactive waste package. Thus, a high confining ability is desirable.For cementitious materials, sealing of cracks may occur in water due to the precipitation of calcium compounds. This can affect the confining ability. In this study, the sealing of a crack in HSULPC in water was investigated using microfocus X-ray computed tomography (CT). The sealing by precipitation occurred only around the end of the specimen. Sealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 19 publications
4
36
1
Order By: Relevance
“…For the control mortar however, they are concentrated close to the top surface. This observation is in agreement with (Fukuda et al 2012), where the healing products distribution is important close to the top surface of a high-strength and ultra-low-permeability concrete specimen cured under seawater.…”
Section: Distribution Of Healing Products Along the Cracksupporting
confidence: 80%
See 3 more Smart Citations
“…For the control mortar however, they are concentrated close to the top surface. This observation is in agreement with (Fukuda et al 2012), where the healing products distribution is important close to the top surface of a high-strength and ultra-low-permeability concrete specimen cured under seawater.…”
Section: Distribution Of Healing Products Along the Cracksupporting
confidence: 80%
“…X-ray tomography is often used to produce 3D images of cementitious materials with or without mechanical loadings, to capture damage and strain localization. Few experimental results exist however related to self-healing (Van Tittelboom et al 2011;Henry et al 2013;Fan et al 2013;Fukuda et al 2012). Van Tittelboom et al (2011) adopted this technique to visually observe the crack and healing agent (polyurethane) distribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also explored various approaches to promote self-healing, such as the use of bacteria, crystalline admixtures, and superabsorbent polymers [13][14][15][16][17][18][19][20][21]. Choi et al reported that a large amount of CaCO 3 precipitate was produced in the surface layer and inside microcracks because the self-healing of cement-based composite materials generated carbon dioxide gas in micrometer-sized ultrafine bubbles, which flowed into microcracks under a continuous water supply [1,22,23].…”
Section: Introductionmentioning
confidence: 99%